Molecular Response in Intestinal and Immune Tissues to in Ovo Administration of Inulin and the Combination of Inulin and Lactobacillus lactis Subsp. cremoris - Dunislawska, Aleksandra; Herosimczyk, Agnieszka; Lepczynski, Adam; Slama, Petr; Slawinska, Anna; Bednarczyk, Marek; Siwek, Maria (Frontiers in Veterinary Science, 2021)
Intestinal microbiota is a key factor in maintaining good health and production results in chickens. It plays an important role in stimulation of immune responses, as well as in metabolic processes and the nutrient digestion. Bioactive substances such as prebiotics, probiotics or their combination (synbiotic) can effectively stimulate intestinal microbiota and therefore replace antibiotic growth promoters. It has been proved that intestinal microbiota might be stimulated at the early stage of embryo development in ovo. The aim of the study was to analyze the expression of genes related to energy metabolism and immune response after the administration of inulin and a synbiotic, in which lactic acid bacteria were combined with inulin in the intestines and immune tissues of chicken broilers. The experiment was performed on male broiler chickens. Eggs were incubated for 21 days in the commercial hatchery. On the day 12 of egg incubation to the egg cell the inulin as a prebiotic and inulin with Lactobacillus lactis subsp. cremoris as a synbiotic were delivered. Control group was injected with physiological saline. On day 35 post hatching, birds from each group were randomly selected and sacrificed. Tissues (spleen, caecal tonsils and large intestine) were collected and intended for RNA isolation. The gene panel (ABCG8, HNF4A, ACOX2, APBB1IP, BRSK2, APOA1 and IRS2) was selected based on the microarray dataset and biological functions of genes related to the energy metabolism and immune responses. Isolated RNA was analyzed with RT-qPCR method and the relative gene expression was calculated. In our experiment, distinct effects of prebiotic and synbiotic following in ovo delivery were manifested in all analyzed tissues with the lowest number of genes with altered expression shown in the large intestines of broilers. Results demonstrated that prebiotic or synbiotic provide a potent stimulation of gene expression in the spleen and caecal tonsils of broiler chickens. It should be noted that the overall number of gene expression levels and the magnitude of their changes in the spleen and caecal tonsils was higher in the group of synbiotic chickens compared to the prebiotic group